Coleridge’s Translucence: A Failed Transcendence? - Wright, Patrick (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractIn this article I explore what I consider to be a fundamental association between Coleridge’s philosophical ideas of polarity, symbol, and translucence, and his more pathological bipolar condition (manic-depressive psychosis and melancholia). I take it that Coleridge’s sublimating theory of polarity (two opposing poles united in their opposition, both struggling against each other, and yet effective by benefit of the other) draws its energy from his psychical and somatic illness, whereby the abyss of squalor that the poet and philosopher recurrently finds himself in is the constitutive pole of his prodigious imagination. Simultaneously, my aim is to problematise what many critics identify as a feminine or non-Oedipal sublime by showing that Coleridge implements such a position, but pays for it with his suffering body. This is not to suggest that the feminine sublime is inevitably pathogenic; rather, my purpose is to critique any overly optimistic valorisation of the excess or alterity it speaks of, and to claim that this otherness at least risks the possibility of psychosis.